Direct inhibition of substantia gelatinosa neurones in the rat spinal cord by activation of dopamine D2-like receptors - Tamae, Akihiro (Blackwell Science Inc, 2005)
Dopaminergic innervation of the spinal cord is largely derived from the brain. To understand the cellular mechanisms of antinociception mediated by descending dopaminergic pathways, we examined the actions of dopamine (DA) on nociceptive transmission by using behavioural studies and whole-cell patch-clamp recordings from substantia gelatinosa (SG) neurones in the spinal cord. Intrathecal administration of DA increased the mechanical nociceptive threshold and this effect was mimicked by a D2-like receptor agonist, quinpirole, but not by a D1-like receptor agonist, SKF 38393. In current-clamp mode of patch-clamp recordings, bath application of DA hyperpolarized the membrane potential of SG neurones and suppressed action potentials evoked by electrical stimulation of a dorsal root. In voltage-clamp mode, DA induced an outward current that was resistant to TTX, was blocked by the addition of Cs(+) or GDP-β-S in the pipette solution, and was inhibited in the presence of Ba(+). The DA-induced current reversed its polarity at a potential close to the equilibrium potential of the K(+) channel calculated from the Nernst equation. The DA-induced outward current was mimicked by quinpirole, but not by SKF 38393. The DA-induced outward current was suppressed by a D2-like receptor antagonist, sulpiride, but not by a D1-like receptor antagonist, SCH 23390. In contrast, DA did not cause any significant change in amplitude and frequency of miniature excitatory postsynaptic currents (mEPSCs). These results indicate that DA mainly acts on postsynaptic SG neurones to induce an outward current via G-protein-mediated activation of K(+) channels through D2-like receptors. This may be a possible mechanism for antinociception by the descending dopaminergic pathway.